Predicting Malignancy in Small Testicular Lesions - Del Real-Valdes, O (Polish Urological Association, 2022)
Introduction Small testicular lesions ≤20 mm (STL) detected by ultrasound (US), usually non-palpable, have been reported to be benign in up to 80% of cases. Thus, partial orchiectomy with or without frozen section examination and surveillance has been advocated for these kinds of lesions. We seek to report the proportion of benign lesions in testicular tumors ≤20 mm detected by US in our population and explore the predicting factors of malignancy. Material and methods A retrospective descriptive study of orchiectomies performed for testicular tumors in patients older than 15 years between 2005 and 2019 was performed, including all patients with lesions ≤20 mm on US imaging. Results A total of 70 patients with STL were included (mean age 34.6 ±10.8 years). Overall, 69% of the lesions were malignant while the smallest lesions (≤10 mm) showed 61% of cancer. Moreover, in the subgroup of non-palpable lesions ≤10 mm, 50% were malignant. Multifocal tumors were found in 18 sub-jects with a malignancy rate of 88%. There was a significant association between maximum size on US, multifocality and malignancy. Neither tumor markers nor palpability foretold a malignant lesion. A predictive model including size and multifocality was created showing a positive predictive value of 83.3%. Conclusions US maximum size and multifocality were predictors of malignancy in STL. However, even the smallest lesions showed a 50% chance of being malignant, thus surgery with or without intraopera-tive biopsy is warranted in most cases. © 2022, Polish Urological Association. All rights reserved.